Indicators of the association of Unemployment in Indonesia with the Level of Employment Opportunity, GDP, and SER - Pambayun, Diesta (LifeSciFi, 2021)
Population inequality and the unequal distribution of income are indicators of unemployment in Indonesia, while unemployment plays an important role in economic growth. The increase in Gross Domestic Product (GDP) means that the level of public welfare improves in direct proportion to the gross domestic product (GDP) which is used as a measuring tool for economic conditions. School Enrollment Rates (SER) and employment opportunities are also identified as having an effect on economic growth, so it is important to conduct research using the ECM method using time series data for 1990-2019 sourced from the Central Statistics Agency (CSA). Based on the results of data processing, it can be seen that in the short and long term employment opportunities and GDP have a positive effect on unemployment. However, in the long term GDP and SER have no significant negative effect on unemployment.